Associations Among Religiosity, Religious Rejection, Mental Health, and Suicidal Ideation in Transgender and Gender Nonconforming Adults - Steph L. Cull; Paul B. Perrin; Richard S. Henry (Behavioral Sciences)
Objectives: Religiosity has generally been shown to be a protective factor against adverse mental health in the general population. Transgender and gender non-conforming (TGNC) individuals, however, may not experience the same protective effects, as many religions are unsupportive of diverse gender identities. This study examined whether increased religiosity and having been rejected by a religious community because of one’s gender identity were associated with mental health issues in TGNC individuals. Methods: A sample of TGNC adults (n = 154), predominantly from the United States, completed an online survey assessing these constructs. Results: These constructs were highly represented in the sample, with 46.1% of participants having experienced religious rejection at some point throughout their lifetime because of their gender identity, 40.3% currently experiencing symptoms of elevated depression and 34.4% of elevated anxiety, and 48.7% with suicidal ideation over the past 2 weeks. Religious rejection was associated with increased depression, anxiety, and suicidal ideation. Neither interpersonal nor intrapersonal religiosity was associated in a bivariate way with any of the three mental health outcomes. However, among participants who experienced rejection by one’s religious community, interpersonal religiosity was strongly associated with increased depression symptoms and suicidal ideation, whereas conversely among TGNC individuals who had not experienced rejection by their religious community, interpersonal religiosity was weakly associated with depression and suicidal ideation. Conclusion: The results underscore the extremely harmful effects of religious rejection due to one’s gender identity on religious TGNC individuals, pointing to the active contributions of the behaviors of traditional religious groups towards TGNC mental health problems and suicide.